2019
DOI: 10.1002/htj.21605
|View full text |Cite
|
Sign up to set email alerts
|

Stagnation flow of hybrid nanoparticles with MHD and slip effects

Abstract: The flow of hybrid nanoparticles with significant physical parameters with different base fluids in the presence of Biot number, velocity slip, and MHD effects has not been explored so far, particularly for a circular cylinder. Therefore, the current report is presented to offer a numerical solution for hybrid nanoparticles with base fluids (water and ethylene glycerol) via a circular cylinder. The physical situation is interpreted in terms of partial differential equations and is converted into ordinary diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Most review studies also ascertained that the hybrid nanofluid contributes to an extra thermal conductivity as compared to the single nanofluid [22][23][24]. Besides, few researchers also have actively investigated the hybrid nanofluid with various flow geometries either on the steady or unsteady flow [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Most review studies also ascertained that the hybrid nanofluid contributes to an extra thermal conductivity as compared to the single nanofluid [22][23][24]. Besides, few researchers also have actively investigated the hybrid nanofluid with various flow geometries either on the steady or unsteady flow [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Raza et al [ 38 ] investigated thermal radiation and slip velocity effects concurrently with a heated convective stretching plate. Abbas et al [ 39 ] exhibited the flow of hybrid nanoparticles with slip velocity and MHD. In the presence of thermal and hydrodynamic slip conditions, Rao et al [ 40 ] proposed the laminar free convective boundary-layer flow of a Casson viscoelastic fluid external to a vertical permeable spherical cone.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies of fluids with slip velocity effect find applications in some systems with fluids where the ratio between the surface and volume is large. [9][10][11][12][13] For instance, Ramesh et al 14 investigated the radiation and Joule heating effects on magnetohydrodynamic (MHD) Carreau fluid with hydrodynamic slip, and in another study, 15 analyzed the effects of slip and Hall current on Jeffrey fluid suspension flow in a peristaltic MHD blood micropump. These slip effects together with entropy production analysis were considered in systems with and without applied external field.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were conducted by Mahian et al 8 where a review of the related studies to the entropy production in nanofluids was shown. In this context, studies of fluids with slip velocity effect find applications in some systems with fluids where the ratio between the surface and volume is large 9‐13 . For instance, Ramesh et al 14 investigated the radiation and Joule heating effects on magnetohydrodynamic (MHD) Carreau fluid with hydrodynamic slip, and in another study, 15 analyzed the effects of slip and Hall current on Jeffrey fluid suspension flow in a peristaltic MHD blood micropump.…”
Section: Introductionmentioning
confidence: 99%